UJI STABILITAS ENZIM LIPASE TERIMOBILISASI PADA KITOSAN SERBUK MELALUI TEKNIK TAUT SILANG - Fandhi Adi Wardoyo; Tri Joko Raharjo; Respati Tri Swasono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Lipase has a great catalytic power, but easily influenced by environments and difficult to separate at the ends of the reaction, so it can not be re-used. Based on that, one solution to overcome that problem is through the enzyme immobilization. Immobilization of lipase on chitosan powder was performed via cross linking technique. Chitosan was prepared from crab shell with deacetylation degree 82,34% and crosslinked with glutaraldehide. The aims of this research is to determine the thermal stability and multiple-use stability through the hydrolysis reaction of palm oil. Immobilized lipase on chitosan powder was able to maintain its activity at 50 oC, and still can produce free fatty acid as much as 48,55%. The immobilized lipase was also able to maintain its activity after multiple-uses up to five reaction cycles, and still can produce free fatty acid as much as 40,82%.Keywords: lipase, immobilization, chitosan, cross linking